2008
DOI: 10.1186/1471-2202-9-15
|View full text |Cite
|
Sign up to set email alerts
|

Potential identity of multi-potential cancer stem-like subpopulation after radiation of cultured brain glioma

Abstract: Background: Glioblastoma multiforme (GBM) is the most frequently encountered brain cancer. Although the existence of cancer stem cells in GBM has been previously established, there is little evidence to explain the difference between cancer stem cells and radio-resistant cells in GBM. In an effort to increase our understanding of whether cellular radio-resistance is a characteristic associated with cancer stem cells, we developed a dissociated cell system of subpopulations derived from GBM, and demonstrated ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 29 publications
3
34
0
6
Order By: Relevance
“…Studies of cultured cells and experimental animal models support this hypothesis. 6,10,13,19 However, the validity of CD133 as a glioma stem cell marker and its clinical ramifications are still controversial. 4 The identification of CD133-negative glioblastoma-derived cancer stem cells has raised the question of whether CD133 serves as a universal enrichment marker for glioma stem cells.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…Studies of cultured cells and experimental animal models support this hypothesis. 6,10,13,19 However, the validity of CD133 as a glioma stem cell marker and its clinical ramifications are still controversial. 4 The identification of CD133-negative glioblastoma-derived cancer stem cells has raised the question of whether CD133 serves as a universal enrichment marker for glioma stem cells.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…16 Estimating possible options for viro-radiotherapy is complicated by the fact that the choice of the suitable radiation technique for recurrent gliomas has to be made individually for ratio of CD-133 + cells increased as a result of IR induced selection. After IR alone, we observed a similar growth pattern in our glioma cell cultures which were different from the cells tested by Kang et al 15 After a high IR dose of 20 Gy subpopulations of cells survived in all our glioma cultures and started to proliferate after a lag period of 7 days. Similar findings could be observed after cytotoxic H-1 treatment, which did not completely eradicate all glioma cells.…”
Section: Previously Irradiated Glioma Cells Remain a Target For H-1pvmentioning
confidence: 47%
“…Lee et al (2011) demonstrated that microRNA-7 increases radiosensitivity of human cancer cells with activated EGFR-associated signaling, and Qu's experiment (Qu et al, 2012) testified that MiR-205 determines the radioresistance of human nasopharyngeal carcinoma by directly targeting PTEN. More studies (Lal et al, 2009;Hu et al, 2010;Ng et al, 2010;Moskwa et al, 2011) revealed that miRNA can impact the radiosensitivity by modulating the expression of key proteins in DNA damage repair pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells are considered to be the source of tumor development and radiation resistance (Hambardzumyan et al, 2006;Blazek et al, 2007;Kang et al, 2008;Ghotra et al, 2009). In recent years, people have successfully separated and identified dozens of cancer stem cells; on the basis of isolated and identified tumor stem cells, some research has gone deep into the level of gene regulation in cancer stem cells.…”
Section: Introductionmentioning
confidence: 99%